“We Are in a Different World”: A Reflection on Science-Policy Interface - Ahmad Maryudi (Jurnal Ilmu Kehutanan, 2018)
President Joko Widodo, during a foresters’ reunion at the Faculty of Forestry-Universitas Gadjah Mada in December 2017– expressed his concerns about deforestation and forest degradation in Indonesia. Talking about the roles of scientists and academia, he was implicitly asking: “Where have you been?” He clearly expected them to show their contribution through producing “impact science”. This offers chances to channel their expertise and gain greater influence in policy-making processes. In fairness, a remarkable number of research programs, networks and collaboration across scientific disciplines have endeavoured to formulate viable strategies for wise use and responsible management of forests (Maryudi & Sahide 2017), although some (e.g. Kartodiharjo 2013) argue that a fraction of scientists may conduct scientific exploration for the sake of science itself. A paradox, there is.We may simplistically say “better science, better policy”. Research through systematic procedures is indeed highly desirable to produce more accurate policy advice (Head & Lucia 2015). But question remains how to integrate scientific results into policy decision-making and implementation processes, and what factors may facilitate or debilitate such processes. We have seen “ready-made” scientific results with great potential to contribute to improving the forest conditions under- presented and even overlooked in policy-making processes. A reality check, it is.In fact, science-based findings and advices are not ulilised, not for reasons of objectivity and truth but because of their conformity and convergence of normative ideas and beliefs of government agencies and policy-makers (Werland 2009). Their decisions are taken in certain directions in the political, social, and economic systems (see Maryudi 2015 for an example), largely by the interest of their powerful and influential constituents (Boecher & Krott 2016). What they expect from science often diverge from scientists’ estimations on what policy-makers consider relevant scientific products (Janse 2008).Political considerations may prohibit the adoption of ample strategies (Maryudi 2016). We have witnessed countless examples (see Maryudi & Krott 2012; Setiawan et al. 2016; Prabowo et al. 2017; Maryudi 2005). As a result, the political decisions often deal with minor changes and waives any comprehensive problem analysis (Krott 2005). Policymakers may use research findings, not as input in decision making, but as a political tool to justify the decisions made. Given the complex policy-making processes, it is a big ask to expect knowledge acquisition. For scientists, producing evidence is very important, but making them applicable, in accordance with the needs and logic of thinking policy makers is equally important.There are ways to improve the impact of their research, nonetheless. Thompson et al. (2011) suggest scientists to focus on public priorities in formulating the research areas. Maryudi et al. (2018) say that scientific agenda may need to balance between issue-driven and curiosity-driven science. This would bridge disconnects between scientific focus and policy priorities. They also need to communicate effectively to wider communities. Scientific information should be easily digested by the target groups; this requires a broader set of skills than the commonly used in scientific communities nonetheless (ibid.). This may well go beyond the capacity of the scientific community because they often have less influence on policy levels. To mediate this, Boecher and Krott (2016) highlight the role of intermediaries capable of transferring knowledge and mediating interests. Werland (2009) scientists may need to seek strategic coalitions with non-forestry actors in order to integrate their findings into policy.